The ethnographic nature of toponyms in the historical work Shezhire-I Terakime - Baltabay Д.; Kaimaz Зеки (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
In linguistics, the definition of the lexical and semantic meaning of toponyms, the differentiation of ethnographic character, and their etymological analysis are of particular importance. Consideration of proper names not only in the semantic aspect, but also in their connection with the worldview of the nation, customs, culture, centuries-old history testifies to the great cognitive activity of the language. The research article provides a semantic analysis of the names of lands and waters of Talas, Zhaiyk, Sairam, Syr, Talgar found in the work Shezhire-i terakime, conclusions on etymology are given, the ethnographic character is differentiated. Attention is drawn to their use in figurative or literal meaning, phonetic differences and morphological features between the Turkic languages, as well as other languages. In phonetic analysis, special importance is attached to sound correspondences (variability), in morphological analysis – creation of roots, appendages, is studied historically. At the same time, a semantic (semantic proximity and discrepancy) comparative analysis of the use of these toponyms to date has been carried out. Since this historical work is one of the monuments of the medieval Chagatai script, there are a large number of linguistic units common to the Turkic languages in its lexical layer. Linguistic features between the Turkic languages belonging to the Kipchak group and the Oguz group are differentiated by conducting diachronic, synchronous analysis on them. In the course of the study, scientific and theoretical conclusions were given based on research, scientific opinions of scientists - Altaists and Turkologists. The study of the ethnographic nature of toponyms, the determination of their historical origin, the demonstration of their scope of application today, the scientific study of them as a phenomenon in the consciousness of the nation indicate the relevance of the article.